Chronic Stress Reduces Sexual Incentive Motivation in Male Mice - Dicky Faizal Irnandi, dr., Sp.And; Samsul Arifin; Daniel Stenly Chandra; Rionanda Vieri; Hikmawan Wahyu Sulistomo (Indonesian Andrology and Biomedical Journal, 2026)
Backgrounds: Chronic stress is an important psychological factor associated with impaired male sexual function. However, experimental evidence regarding its effect on the motivational component of sexual behavior remains limited. The Sexual Incentive Motivation test can evaluate female-directed sexual motivation without direct copulatory contact. Aims: This study aimed to evaluate the effect of chronic unpredictable mild stress on sexual incentive motivation in male mice and to observe whether post-stress Tribulus terrestris intervention was associated with behavioral restoration. Methods: This experimental laboratory study used a randomized posttest-only control group design. Twenty-four healthy male BALB/c mice aged 8-10 weeks were randomly allocated into four groups: control, chronic unpredictable mild stress, placebo recovery, and Tribulus terrestris intervention. The chronic stress, placebo recovery, and Tribulus terrestris groups were exposed to chronic unpredictable mild stress for four weeks. The placebo recovery and Tribulus terrestris groups then underwent an additional two-week post-stress period before behavioral assessment. Sexual motivation was evaluated using an EthoVision-based Sexual Incentive Motivation arena for 10 minutes. The observed parameters were total distance moved, female-zone frequency, and female-zone cumulative duration percentage. Results: Chronic stress was associated with reduced locomotor activity and lower female-directed sexual incentive behavior. The placebo recovery group showed a behavioral pattern similar to the stressed group, suggesting limited spontaneous recovery. The Tribulus terrestris group demonstrated higher female-zone exploration and duration, indicating improved female-oriented sexual incentive motivation after stress exposure. Conclusions: Chronic unpredictable mild stress reduced sexual incentive motivation in male mice. Post-stress Tribulus terrestris intervention was associated with improved female-directed exploratory behavior.